Highly Sensitive Minimal Residual Disease Detection by Biomimetic Multivalent Aptamer Nanoclimber Functionalized Microfluidic Chip. Issue 20 (22nd April 2020) - Liu, Yilong; Zhang, Huimin; Du, Yahui; Zhu, Zhi; Zhang, Mingxia; Lv, Zhehao; Wu, Lingling; Yang, Yuanyuan; Li, Ao; Yang, Liu; Song, Yanling; Wang, Sili; et al.
Abstract: Minimal residual disease (MRD) offers a highly independent prognostic factor for leukemia patients. However, challenges confronting conventional MRD assays are high invasiveness, as well as limited detection sensitivity and clinical applicability. Inspired by the self‐adaptive skeleton and multiple suckers or tendrils of climbing plants, a biomimetic Multivalent Aptamer Nanoclimber (MANC)‐functionalized microfluidic chip (MANC‐Chip) is reported for minimally invasive, highly sensitive and clinically applicable MRD detection in the peripheral blood of T‐cell acute lymphoblastic leukemia patients. The MANCs are synthesized by a simple co‐polymerization reaction. Due to their flexible structure and cooperative multivalent effect, MANCs dramatically enhance the binding affinity of aptamers targeting leukemia cells. A deterministic lateral displacement‐patterned microfluidic chip is designed to further increase the collision probability between MANCs and leukemia cells. Benefiting from the synergistic effect of multivalent binding and enhanced collision, a high capture efficiency of 92.2% for leukemia cells is achieved. Moreover, the captured leukemia cells can be released with high efficiency of 88.9% and high viability of 93.8% via nuclease treatment prior to downstream analysis. Overall, the excellent features of MANC‐Chip make it very useful for precise detection of MRD and better understanding of leukemia. Abstract : Highly sensitive minimal residual disease detection is carried out by biomimetic multivalent aptamer nanoclimber‐functionalized microfluidic chip.